Forestry Sector Impact on the Economy of Central Java, Indonesia - Firmansyah, Firmansyah; Kurnia, Akhmad Syakir; Oktavilia, Shanty; Prayogi, Ryan (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
In 2016, the forestry sector produced a Gross Regional Domestic Product (GRDP) of Rp. 3.8 trillion or around 0.45% of the total GRDP of the province of Central Java, Indonesia (BPS Central Java, 2017). The Forestry Sector growth has increased, but the role of the sector shows a downward trend in GRDP. By employing the Input-Output analysis, this study intends to identify the structure of the Central Java forestry sector, through backward and forward linkages and mapping the path of the impact of the forestry sector's economic activities through simulations, toward the economy and sectoral income levels in Central Java. This study finds that the forestry sector is intermediate ouput that is used by other sectors to become their production inputs, so this sector has a good multiplier for the economy.